2007
DOI: 10.1097/qad.0b013e3280187505
|View full text |Cite
|
Sign up to set email alerts
|

Diminished efficiency of HIV-1 reverse transcriptase containing the K65R and M184V drug resistance mutations

Abstract: The simultaneous presence of K65R and M184V in reverse transcriptase has a negative impact with regard to the efficiency of initiation of (-)ssDNA synthesis and RNA usage, that exceeds the effect of either mutation on its own. These mechanisms, among others, are responsible for the diminished viral replicative capacity observed in tissue culture when K65R/M184V-containing viruses are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
44
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 55 publications
9
44
1
Order By: Relevance
“…Previous studies have shown that M184V added to a TAM background reduced excision on RNA templates (32,48,58,62) and DNA templates (9,21,22,27,38,49,62) by 16 to 58%, though no decrease was detected in one study (39). We found the effect on a DNA template to be variable, ranging from no effect to a 34% decrease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that M184V added to a TAM background reduced excision on RNA templates (32,48,58,62) and DNA templates (9,21,22,27,38,49,62) by 16 to 58%, though no decrease was detected in one study (39). We found the effect on a DNA template to be variable, ranging from no effect to a 34% decrease.…”
Section: Discussionmentioning
confidence: 99%
“…K65R is also a suppressor of AZT resistance by TAMs (6,36,43,59), and AZTMP excision activity is reduced in RTs containing this mutation (21,36,59). In contrast to the results obtained with M184V, the addition of K65R to the RT D67N/K70R/T215Y/K219Q background reduced AZTMP excision activity to similar extents on both DNA (Fig.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…64 Furthermore, the presence of the M184V/I mutation typically results in impaired viral replication capacity, which has been shown to decrease HIV RNA levels by about 0.5 logs. 65,66 When ABC + 3TC are used in combination with another class, the M184V mutation typically appears first and most frequently; the K65R mutation and L74V mutation are seen much less frequently. The abacavir-selected mutations K65R, L74V and Y115F each individually confer about three-to fourfold resistance to ABC, but in combinations of 2 or 3, they confer up to 8-to 10-fold resistance.…”
mentioning
confidence: 99%